Success factors of transformative learning: putting theory into practice. Issue 6 (1st November 2020) - Schnitzler, Tobias
ABSTRACT: This paper elaborates on a number of key success factors of transformative learning (TL) theory as well as provides arguments that validate them. The paper at hands lines out how transformative learning can improve teams in start-ups and NGOs to the direction of education for sustainable development (ESD). Moreover, social structures and belief systems can influence learning in a way that learners make transformation of their experiences in various means. It exemplifies how Mezirow's theory can be put into practice and includes results from collaborative and social learning, personal transformation, team spirit as well as learning environments. The case studies make use of new skills and values via guided interviews. Data from 42 qualitative interviews are analysed and used to argument that transformative learning can be practiced, with success factors, in start-ups and NGOs.